Ampullariid gastropods from the Palaeogene Hudi Chert Formation (Republic of the Sudan). (May 2017) - Harzhauser, Mathias; Neubauer, Thomas A.; Bussert, Robert; Eisawi, Ali A.M.
Abstract: The age of the Hudi Chert fauna is highly controversial and crucial for the reconstruction of the geological history of the Nile valley. Herein, six species of Ampullariidae (Gastropoda) are described from the Hudi Chert Formation in the Republic of the Sudan, documenting that alleged relations of the Hudi Chert fauna with Oligocene faunas from Egypt turned out to be based on misidentifications. Although an Oligocene age cannot be excluded, we propose an Eocene age for the Hudi Chert fauna based on the known stratigraphic range of the newly established genus Sudanistes . A Neogene age is clearly excluded based on the presence of the exclusively Palaeogene genus Pseudoceratodus . The Hudi Chert ampullariids lived in an extensive freshwater system of swamps and ponds, whereas riverine conditions and deep lake setting are unlikely depositional environments. Pila busserti Harzhauser & Neubauer is described as a new species and Sudanistes Harzhauser & Neubauer is introduced as a new genus. Graphical abstract: Highlights: A lacustrine gastropod assemblage from the Hudi Chert Formation is described. The Hudi Chert Formation is probably of Eocene age. The wetland environments predate the development of the Nile drainage system. Sudanistes is a new Ampullariidae genus characteristic of the African Paleogene.